Kekondusifan Pembelajaran Online terhadap Etika dan Moral di Lingkungan Fakultas Bahasa dan Seni Universitas Negeri Medan - Chairun Nisa; Salwa Andini; Sri Yunita; Muthi’ah Lathifah (Journal on Education, 2023)
The online learning system (in the network) is a learning system without face-to-face meetings between teachers and students but is carried out online using the internet network. The teacher must ensure that teaching and learning activities continue, even though students are at home. The solution is that teachers are required to be able to design instructional media as innovations by utilizing online media. According to KBBI, ethics is the science of what is good and bad and about moral rights and obligations (morals). A good understanding of digital ethics will be able to reduce hoaxes, bullying, cyberbullying, hate speech, and leakage of personal data. Morals are the customs of the rules of decency. Benchmarks in behaving morally in accordance with values, ethics, or decency in accordance with the values of the rules or truth. Therefore this study aims to awaken students in morality and ethics even though the lessons take place online.